Surgically removal of maxillary impacted canine: labial and palatal approach - Andi Tajrin; Faisal (Makassar Dental Journal PDGI Makassar, 2020)
Background: The maxillary canines most frequently to be involved in eruption problem and become impacted following maxillary and mandibular thirdmolars. When impacted maxillary canines have unfavorable position or they are not susceptible to orthodontic traction or reimplantation, surgical extraction isthe most appropriate treatment. Objective: Report a surgical removal of impacted maxillary canine which accessed both labially and palatally. Case: A 19-years-old woman came to the oral and maxillofacial clinic complained her left upper anterior tooth missing and reported mild pain around the area since twoyears ago. There was a fluctuation on the labial mucosa. Panoramic radiograph confirmed the horizontal impaction of the maxillary left canine. Conclusion:The maxillary canine was removed by surgery under under local anesthesia.